Targeting financial stability: Macroprudential or monetary policy? - David Aikman; Julia Giese; Sujit Kapadia; Michael McLeay (European Central Bank (ECB), 2019)
This paper explores monetary-macroprudential policy interactions in a simple, calibrated New Keynesian model incorporating the possibility of a credit boom precipitating a financial crisis and a loss function reflecting financial stability considerations. Deploying the countercyclical capital buffer (CCyB) improves outcomes significantly relative to when interest rates are the only instrument. The instruments are typically substitutes, with monetary policy loosening when the CCyB tightens. We also examine when the instruments are complements and assess how different shocks, the effective lower bound for monetary policy, market-based finance and a risk-taking channel of monetary policy affect our results.
Keywords: E52; E58; G01; G28; 330; macroprudential policy; monetary policy; financial stability; countercyclical capital buffer; financial crises; credit boom